Biotherapeutics and Antibiofilm Properties of Sponge-Associated Bacteria from Tanjung Tiram Mangroves, Southeast Sulawesi - Mamangkey, Jendri; Sunarto, Sunarto; Fadjri, Corrina Lailatul; Irawan, Herman; Huda, Muhammad Komarul; Wibowo, Des Saputro; Mutiara, Ilma (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2025)
The search for new therapeutic agents has increasingly focused on bioactive compounds from sponge-associated bacteria. This study investigated bacterial symbionts of marine sponges collected from the mangrove ecosystem of Tanjung Tiram, Southeast Sulawesi, which have not been previously explored for their bioactive potential. Thirty bacterial isolates were screened in triplicate for antibacterial, antioxidant, antidiabetic, and antibiofilm activities. Antibacterial activity was evaluated using the disc diffusion method, antioxidant capacity by DPPH radical scavenging assay, α-glucosidase inhibition for antidiabetic potential, and antibiofilm activity by the crystal violet binding method. Several isolates showed notable bioactivities: strain Sp.8 produced the largest inhibition zone against Escherichia coli (15 mm), and Sp.14 showed the strongest inhibition against Staphylococcus aureus (23 mm). The most active antioxidant strains (Sp.14, Sp.15, Sp.13, and Sp.6) exhibited radical scavenging activity above 80%, while Sp.13, Sp.15, Sp.31, and Sp.37 showed high α-glucosidase inhibition (>74%). Strains Sp.38 and Sp.12 significantly reduced biofilm formation by E. coli and S. aureus, respectively. These findings reveal the untapped potential of sponge-associated marine bacteria from Tanjung Tiram as promising sources of bioactive metabolites for future drug discovery.